Synthesis, CYP 450 evaluation, and docking simulation of novel 4‐aminopyridine and coumarin derivatives. Issue 3 (14th January 2019) - Ghalehshahi, Hajar G.; Balalaie, Saeed; Sohbati, Hamid R.; Azizian, Homa; Alavijeh, Mohammad S.
Abstract: Four series of novel compounds based on 4‐aminopyridine, glatiramer acetate, pyrone, and coumarin backbones were sufficiently synthesized and identified by spectroscopic methods. CYP enzyme inhibition assays of five predominate human P450 isozymes indicate that all compounds, except for 4‐hydrazide pyridine1c, seem to be less toxic than 4‐aminopyridine. Further investigation of the compounds using molecular docking experiments revealed different, the same, or stronger binding modes for most of the synthesized compounds, with both polar and hydrophobic interactions with the 1WDA and 1J95 receptors compared to benzoyll ‐arginine amide and 4‐aminopyridine, respectively. These results introduce the synthesized compounds as K + channel blockers that could be considered for in vivo CNS disease studies. Abstract : A series of novel compounds based on the structure of 4‐aminopyridine, glatiramer acetate, and coumarin via C–N bond formation were synthesized and their toxicities, K + channel blocker affinities and PAD4 inhibitory activities were investigated compared to 4‐aminopyridine as a known CNS drug. All compounds, except for 4‐hydrazide pyridine, seem to be less toxic than 4‐aminopyridine.